Characterization of Some Cobalt(II) Complexes Derived from Heterocyclic Ligands 3-Methyl-4-Nitro-1- (para-Nitrophenyl)-5-Pyrazole and Imidazoles - Narain, Gopal; Sufal Kumar Naidu, S.; Kumar Jain, Jai (Asian Journal of Chemistry, 2010)
Some octahedral complexes ot the 3-methyl-4-nitro-1-(para-nitrophenyl)-5-pyrazolonate, acetate and sulphates of cobalt(II) with imidazoles have been prepared and characterised. The general molecular formulae arrived on the basis of analytical data are [Co(pyrazole)2(imd)4], [Co(CH3COO)2(imd)4], [Co(H2O)4(imd)2]SO4 and [Co(imd)6]SO4, where imd ═ imidazole, 2-methyl-imidazole or benzimidazole. The infrared, magnetic and electronic data of the complexes are discussed in the light of the structures assigned.